2007
DOI: 10.30843/nzpp.2007.60.4597
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and germination phenology of grass weeds and implications for their control in cereals

Abstract: Seeds of Italian ryegrass perennial ryegrass wild oat winter wild oat phalaris and barnyard grass collected during the 2005/06 season were tested for dormancy and germination phenology between April and December 2006 In laboratory and outdoor environments dormancy was widespread in grass weed but not in ryegrass seeds The seeds of grass weeds had better germination in the outdoor environment than the laboratory In the outdoor environment only 15 of wild oat and winter wild oat 1963 of phalaris and 39 of barnya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…The germination of seeds collected only from the poor-soil habitat was affected by light and temperature. The results obtained for the seeds collected from the less fertile habitat are consistent with those reported in earlier studies in which the germination capacity of P. arundinacea reached a level of 80% at a temperature of 20°C under a variable photoperiod (12 h light / 12 h darkness) [18]. In turn, Lindig-Cisneros and Zedler [19] reported higher germination capacity of seeds of this species in the dark and assumed that light might be a germinationinhibiting factor.…”
Section: Discussionsupporting
confidence: 90%
“…The germination of seeds collected only from the poor-soil habitat was affected by light and temperature. The results obtained for the seeds collected from the less fertile habitat are consistent with those reported in earlier studies in which the germination capacity of P. arundinacea reached a level of 80% at a temperature of 20°C under a variable photoperiod (12 h light / 12 h darkness) [18]. In turn, Lindig-Cisneros and Zedler [19] reported higher germination capacity of seeds of this species in the dark and assumed that light might be a germinationinhibiting factor.…”
Section: Discussionsupporting
confidence: 90%
“…The latter strategy maximizes the possibility of finishing the species reproductive cycle whereas the former optimizes the likeliness of escaping early weed control operations. This is consistent with field observations with herbicide applications (Kon et al 2007;Scursoni et al 2007).…”
Section: Life-trait Effectsupporting
confidence: 91%
“…Seeds of plants must be exposed to high temperatures in the summer months (Baskin and Baskin, 1998). In Phalaris arundinacea better germination was observed in 16 hours of lighting (Lindig-Cisneros and Zedler, 2001), but in another study it has been reported that the best temperature was 20° C as well as light regime of 12 h in dark conditions (Kon et al, 2007). The germination and maturity responses to latitude, elevation, soil moisture, soil nutrients, temperature and vegetation density of habitat destruction are different (Baskin and Baskin, 1998).…”
Section: Resultsmentioning
confidence: 98%